2014
DOI: 10.1179/1351000214y.0000000108
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2-mediated antioxidant response by ethanolic extract ofSida cordifoliaprovides protection against alcohol-induced oxidative stress in liver by upregulation of glutathione metabolism

Abstract: Objective The study aimed to evaluate the antioxidant property of ethanolic extract of Sida cordifolia (SAE) on alcohol-induced oxidative stress and to elucidate its mechanism of action. Methods Male albino rats of the Sprague-Dawley strain were grouped into four: (1) control, (2) alcohol (4 g/kg body weight), (3) SAE (50 mg/100 g body weight), and (4) alcohol (4 g/kg body weight) + SAE (50 mg/100 g body weight). Alcohol and SAE were given orally each day by gastric intubation. The duration of treatment was 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Nrf2/HO-1 activation also exerts renoprotective role in alcohol-induced oxidative stress in liver (Rejitha et al 2014) and cerebral ischemic injury (Zhao et al 2014). At cellular and molecular levels, recent studies have demonstrated that CUR attenuates ROS generation and activates signaling pathways that involve the release of Nrf2, promoting transcription of genes that induce the expression of antioxidant system (Shehzad and Lee 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Nrf2/HO-1 activation also exerts renoprotective role in alcohol-induced oxidative stress in liver (Rejitha et al 2014) and cerebral ischemic injury (Zhao et al 2014). At cellular and molecular levels, recent studies have demonstrated that CUR attenuates ROS generation and activates signaling pathways that involve the release of Nrf2, promoting transcription of genes that induce the expression of antioxidant system (Shehzad and Lee 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Recently, studies inducing the expression of antioxidant genes through the activation of Nrf2 using naturally occurring or artificially synthesized small molecules have been conducted [45][46][47]. It was found that Nrf2 has a protective effect against alcohol-induced acute liver injury and carbon tetrachloride-induced liver injury, and that the expression of Nrf2 transcription factor is increased due to oxidative stress by CYP2E1 in hepatocytes [48,49]. Under oxidative stress, oxidative modification of Keap1 allows Nrf2 to release from Keap1, and then Nrf2 translocates into the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…In order to explore the mechanism, the influence of VC-IV on Nrf2/ARE pathway was examined in this study. Under homeostatic conditions, Nrf2 is present in the cytoplasm attaching to a cytosolic protein Keap1, which functions as a suppressor of Nrf2 by retaining it in cytosol and enhancing its proteasomal degradation via ubiquitination [33,34]. But upon activation, Nrf2 acts as a key transcriptional factor that triggers the ARE pathway, and in turn regulates the expression of several antioxidant and phase II detoxifying enzymes [33].…”
Section: Discussionmentioning
confidence: 99%
“…Under homeostatic conditions, Nrf2 is present in the cytoplasm attaching to a cytosolic protein Keap1, which functions as a suppressor of Nrf2 by retaining it in cytosol and enhancing its proteasomal degradation via ubiquitination [33,34]. But upon activation, Nrf2 acts as a key transcriptional factor that triggers the ARE pathway, and in turn regulates the expression of several antioxidant and phase II detoxifying enzymes [33]. Consistent with the results from other studies, the results of the present study showed that HO1 and NQO1 expression in the CDDP-treated group was lower than those of vehicle-treated mice.…”
Section: Discussionmentioning
confidence: 99%